2011
DOI: 10.1097/wnr.0b013e32834d0bc8
|View full text |Cite
|
Sign up to set email alerts
|

Methamphetamine-induced vascular changes lead to striatal hypoxia and dopamine reduction

Abstract: Methamphetamine (meth) is a potent psychostimulant known to cause neurotoxicity. Clinical reports suggest meth abuse is a risk factor for Parkinson’s disease. We investigated changes in the blood brain barrier and cerebral vasculature as a mechanism underlying this risk in rats treated acutely and trained to self-administer meth. We observed blood brain barrier leakage in rats treated acutely with meth. Hypoperfusion in the striatum was detected with acute and chronic meth treatment and associated with hypoxia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
36
1
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(42 citation statements)
references
References 25 publications
4
36
1
1
Order By: Relevance
“…This may not be entirely surprising given that METH administration causes ischemic-like hypoxia. 49 The consequences of METH-induced BBB disruption are many-fold and, as mentioned in later sections, chronic METH exposure in escalating dosing regimen (2.5-10 mg/kg over 3 weeks) aggravates CNS infiltration of viral and microbial pathogens, resulting in decreased survival rates of mice. 80 Strikingly, METH (10 nM-10 mM range) potentiates CNS infiltration of leukocytes across the BBB in various in vitro studies either by disruption of TJ proteins 64,65,73 or enhancement of transcytosis, 71 possibly through increased production of cytokines such as TNFa.…”
Section: Meth Abuse and Blood-brain Barrier Dysfunctionmentioning
confidence: 98%
See 1 more Smart Citation
“…This may not be entirely surprising given that METH administration causes ischemic-like hypoxia. 49 The consequences of METH-induced BBB disruption are many-fold and, as mentioned in later sections, chronic METH exposure in escalating dosing regimen (2.5-10 mg/kg over 3 weeks) aggravates CNS infiltration of viral and microbial pathogens, resulting in decreased survival rates of mice. 80 Strikingly, METH (10 nM-10 mM range) potentiates CNS infiltration of leukocytes across the BBB in various in vitro studies either by disruption of TJ proteins 64,65,73 or enhancement of transcytosis, 71 possibly through increased production of cytokines such as TNFa.…”
Section: Meth Abuse and Blood-brain Barrier Dysfunctionmentioning
confidence: 98%
“…61 Moreover, clinical findings from abstinent METH abusers suggest a long-lasting loss of BBB integrity and cerebrovascular functions. 61 Additionally, Kousik et al 49 have documented a sustained increase in rat striatal endothelin-1 (a vasoconstrictor implicated in stroke pathogenesis) even after discontinuation of METH self-administration for 10 days. Thus, BBB dysfunction is a long-term cerebrovascular complication that is evident during various phases of METH abuse/addiction in humans and rodent models.…”
Section: Meth Abuse and Blood-brain Barrier Dysfunctionmentioning
confidence: 99%
“…mCT analysis was evaluated in the striatum, primary motor cortex, NAc, substantia nigra, VTA, and parietal association cortex. The striatum was assessed in the present study as our prior work showed hypoperfusion uniquely in this brain region after Meth self-administration using the same protocol used here (Kousik et al, 2011). We also assessed vascular alterations in the substantia nigra, the region of origin for striatal afferents, and primary motor cortex, which receives inputs from the striatum.…”
Section: Resultsmentioning
confidence: 99%
“…The striatal selectivity of Meth-induced neurovascular dysregulation, both in human Meth abusers (Chung et al, 2010) and in laboratory rats (Kousik et al, 2011), is striking. This suggests that Meth alters localized blood flow through regionally unique neurovascular units (NVUs), which contain neurons, glia, astrocytes, and vascular endothelial cells (Koehler et al, 2009;Lecrux and Hamel, 2011).…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation